Efficient penetration of ceric ammonium nitrate oxidant‐stabilized gamma‐maghemite nanoparticles through the oval and round windows into the rat inner ear as demonstrated by MRI. Issue 7 (30th May 2016) - Zou, Jing; Ostrovsky, Stella; Israel, Liron L.; Feng, Hao; Kettunen, Mikko I.; Lellouche, Jean‐Paul (Moshe); Pyykkö, Ilmari
Abstract: We aimed to evaluate the magnetic resonance imaging (MRI) contrast effect and delivery efficiency through the middle ear into the inner ear using novel super‐paramagnetic maghemite (γ‐Fe2 O3 ) nanoparticles (NPs) generated using ceric ammonium nitrate (CAN)‐mediated oxidation of Fe3 O4 NPs (CAN–γ‐Fe2 O3 NPs). The CAN–γ‐Fe2O3 NPs, having hydrodynamic diameters of 50–60 nm and potentials of +55.2 mV, displayed super‐paramagnetic behavior characterized by a saturation magnetization Ms of 75.2 emu/g NPs. The r1 and r2* relaxivity (curve slopes) values were 0.0015 and 189 mmol −1  s −1, respectively, indicating strong T2* relaxation maghemite‐based NPs. The CAN‐γ‐Fe2 O3 NPs were stable in the 7.0 T magnetic field. At 3 h after the tympanic medial wall administration, the NPs had significantly located to the cochlea and vestibule. The signal started to recover at 6 h in the ipsilateral cochlea and by 2 d in the vestibule post‐administration. There was no difference in the signal intensity between the left and right ears on the 14th d. Prussian blue staining for iron demonstrated NP distribution in the inner ear tissue. The novel CAN–γ‐Fe2 O3 NPs are a strong MRI T2 contrast agent and penetrated the round and oval windows and have potential application in the molecular imaging of the inner ear. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1883–1891, 2017.